Validity of PIRO Score as an Assessment Tool for Mortality Risk of COVID-19 Pneumonia among Patients Admitted to World Citi Medical Center from March to August 2020. A Retrospective Observational Cohort Study - Graciano, D. Natividad III; Edmart, Pastrana; Rizalyn, Piñera (International Journal of Coronaviruses, 2021)
Introduction In December 2019, cases of serious illness causing pneumonia and death were first reported in Wuhan, China.2 The clinical features of Corona Virus Disease-19 (COVID-19) are ranging from asymptomatic to multi organ dysfunction. The disease can progress to pneumonia, respiratory failure and death.4 Thus, a tool is needed that can predict the severity and in-hospital mortality risk of a patient with COVID-19 Pneumonia. The PIRO (predisposition, insult, response, and organ dysfunction) scoring was developed for use in the emergency department to risk stratify sepsis cases.15 Eventually it was adapted in pneumonia cases to predict its severity. Objective To validate PIRO score as an assessment tool for COVID-19 mortality risk among patients with confirmed COVID-19 RT-PCR test among patients aged 19 and above admitted in World Citi Medical Center from March 2020 to August 2020 Methods This study included 93 patients aged 19 and above admitted in World Citi Medical Center with a primary diagnosis of COVID-19 Confirmed with pneumonia between March 2020 to August 2020. The patients’ charts were retrieved from the hospital medical records and case notes were reviewed. A severity assessment score was developed based on PIRO score (Predisposition comorbidities and age; Insult multilobar opacities and viremia; Response shock and hypoxemia; Organ Dysfunciton) were extracted. The patients were stratified in four levels of risk: a)Low,0-2 points; b)Mild,3 points; c)High,4 points; d)Very High,5-8 points. The PIRO score and the clinical outcome were compared. The discriminative ability of PIRO score to predict mortality risk was evaluated under receiver operating characteristic curve (AUC). Results The PIRO score had an excellent predictive ability for in-hospital mortality (AUC0.9197). Analysis of variance showed that higher levels of PIRO scores were significantly associated with higher mortality (p<0.001). Patients with Mild PIRO risk category were 98.65% less likely to expire (p<0.001, 95%CI 0.0015) and High PIRO risk category were 94.47% less likely to expire (p<0.001, 95%CI 0.0124), both compared to patients with Very high PIRO risk category. Finally, Very High PIRO risk category were more than 44 times likely to expire compared to patients with Low, Mild and High PIRO risk category (p<0.001, 95%CI 11.738). Conclusions The PIRO score is a valid risk model that can be used to predict in-hospital mortality, that can help clinicians provide timely and accurate assessment, and hence appropriate management to patients with COVID-19 Pneumonia.
Keywords: COVID-19; PIRO; Pneumonia